Analysis of colorectal cancer glyco‐secretome identifies laminin β‐1 (LAMB1) as a potential serological biomarker for colorectal cancer. Issue 22 (26th October 2015) - Lin, Qifeng; Lim, Hannah S.R.; Lin, Hui Ling; Tan, Hwee Tong; Lim, Teck Kwang; Cheong, Wai Kit; Cheah, Peh Yean; Tang, Choong Leong; Chow, Pierce K. H.; Chung, Maxey C. M.
Abstract : The high mortality rate in colorectal cancer is mostly ascribed to metastasis, but the only clinical biomarker available for disease monitoring and prognosis is the carcinoembryonic antigen (CEA). However, the prognostic utility of CEA remains controversial. In an effort to identify novel biomarkers that could be potentially translated for clinical use, we collected the secretomes from the colon adenocarcinoma cell line HCT‐116 and its metastatic derivative, E1, using the hollow fiber culture system, and utilized the multilectin affinity chromatography approach to enrich for the secreted glycoproteins (glyco‐secretome). The HCT‐116 and E1 glyco‐secretomes were compared using the label‐free quantitative SWATH‐MS technology, and a total of 149 glycoproteins were differentially secreted in E1 cells. Among these glycoproteins, laminin β‐1 (LAMB1), a glycoprotein not previously known to be secreted in colorectal cancer cells, was observed to be oversecreted in E1 cells. In addition, we showed that LAMB1 levels were significantly higher in colorectal cancer patient serum samples as compared to healthy controls when measured using ELISA. ROC analyses indicated that LAMB1 performed better than CEA at discriminating between colorectal cancer patients from controls. Moreover, the diagnostic performance was further improved when LAMB1 was used in combination with CEA.